Instrumen Kecemasan Akademik: A Systematic Literature Review - Rahmawati, Elin Maulida; Ahman; Sunarya, Yaya (COUNSELIVE: Jurnal Konseling Kehidupan, 2025)
Academic anxiety is a feeling of tension and apprehension toward all possible outcomes that may occur, thereby disrupting academic processes such as examinations, assignments, and learning activities that require high levels of adaptation to academic demands. This condition can interfere with emotional balance, reduce concentration and motivation, and negatively affect students’ academic performance. This study aims to analyze the instruments used to measure academic anxiety. The research employed a Systematic Literature Review (SLR) method using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) model. Out of 26 articles identified, only 7 articles met the inclusion criteria and were analyzed further. The findings indicate that the Spielberger Test Anxiety Inventory (STAI) is the most frequently used instrument among researchers due to its high reliability and widespread international use, although it primarily measures general anxiety rather than academic anxiety specifically. It can be concluded that there is still a need for the development of measurement instruments that are more contextual and specific to academic situations, in order to more accurately capture the cognitive, emotional, and physiological aspects of students’ academic anxiety.